"Saber tratar bien". Natural Water Springs and Human/Non-Human Relations in the Indigenous Practice of Salt Cutting in the Argentine Puna - Miranda Pérez, José María (2026)
This article examines the relation between ojos de agua (springs) and the salt workers of San Miguel de Colorados, Northwestern Argentina, focusing on cutting salt blocks. Based on ethnographic research, it shows that the ojos de agua are conceived both as subterranean springs and as powerful entities with agency, central to this socioproductive activity. Rather than being defined only as «natural water sources» they are recognized as presences endowed with will and the capacity to affect. These attributes reveal a local ontology guided by relational and pluralist principles, where agency is distributed across the visible and invisible world. Within this framework, an apparently economic practice takes on cosmological and ethical dimensions through its entanglement with nonhuman others.